A new method to determine fracture resistance curve of steel under various in-plane loading. (1st May 2021) - Wang, Yanlin; Wang, Weigang; Zhang, Bohua; Li, Chun-Qing
Highlights: A new method to establish  J -R curve for steel under in-plane loading is developed. The crack extensions measured by the developed method are verified. The crack propagation varies significantly under different loading modes. The crack occurs as tensile type or shear type under different loading modes. Both J c  and   δ c decrease with the increase of the components of mode-II loading. Abstract: Methods to establish the fracture resistance curves for ductile materials have been standardised only for mode-I fracture tests. However, the failures of engineering structures can be caused by various loading modes due to the complex loading conditions or inclined crack-like flaws. This paper develops a new method to construct the fracture resistance curves for ductile steels under different in-plane loading, based on the digital image correlation technique. Fracture tests are conducted on compact-tension-shear specimens made of ductile steel. The crack extension and fracture initiation are determined from the strain field of the cracked specimens, and the critical values of J -integral and crack tip opening displacement (CTOD) at the fracture initiation point are determined. Test results show that the fracture initiation point can be captured by the sharp drop of strain near the crack tip, and that the corresponding critical J -integral and CTOD decrease with the increase of the shear load. The merit of the developed method is that the fracture resistance curves parameters can be easily and accurately determined for ductile steels under different in-plane loading.